What is quality in a PhD dissertation in mathematics education? - Niss, Mogens (NOMAD Nordic Studies in Mathematics Education, 2010)
The present paper discusses the issue of quality in PhD dissertations in mathematics education on the basis of the author’s reflections, observations and experiences as a supervisor and as an assessor of PhD dissertations in several countries during the last three decades. Thus, the paper represents the personal stances and views of the author and does not claim to be written on behalf of any segment of the community of researchers in mathematics education. Two major components of quality in a PhD dissertation are being dealt with, quality of the underlying research, and quality of the dissertation as a reflective report of this research and its outcomes. Particular attention is being paid to the issue of what should cause a dissertation to be rejected. The paper emphasises, at the end, that because of the multiplicity of research paradigms and philosophies in research in mathematics education there is no royal road to quality in a PhD dissertation. Therefore, the student cannot avoid involving him- or herself in independent in-depth thinking.